2017
DOI: 10.1186/s12884-016-1213-4
|View full text |Cite
|
Sign up to set email alerts
|

A realist review of the partograph: when and how does it work for labour monitoring?

Abstract: BackgroundThe partograph (or partogram) is recommended by the World Health Organisation (WHO), for monitoring labour wellbeing and progress. Concerns about limitations in the way the partograph is used in the clinical context and the potential impact on its effectiveness have led to this realist systematic review of partograph use.MethodsThis review aimed to answer two key questions, 1) What is it about the partograph that works (or does not work); for whom does it work; and in what circumstances? 2) What are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 48 publications
(86 reference statements)
2
74
2
1
Order By: Relevance
“…Although most healthcare providers working in maternity settings know about the partograph, it is frequently used retrospectively for recording purposes instead of providing prospective support for clinical decision making. Possible reasons for these shortcomings include difficulties in its use and interpretation 26, 27. Our findings suggest that the poor predictive performance of the partograph – and the consequent effect in supporting effective decision making – could contribute to the lack of interest in using the tool prospectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most healthcare providers working in maternity settings know about the partograph, it is frequently used retrospectively for recording purposes instead of providing prospective support for clinical decision making. Possible reasons for these shortcomings include difficulties in its use and interpretation 26, 27. Our findings suggest that the poor predictive performance of the partograph – and the consequent effect in supporting effective decision making – could contribute to the lack of interest in using the tool prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons for these shortcomings include difficulties in its use and interpretation. 26,27 Our findings suggest that the poor predictive performance of the partographand the consequent effect in supporting effective decision makingcould contribute to the lack of interest in using the tool prospectively.…”
mentioning
confidence: 93%
“…The evidence of its effectiveness is inconclusive, a Cochrane review suggested that overall use of the partograph did not significantly impact on a number of specified outcome. 17 Authors also, by our observation are doubtful of its effective use and application. The partogram was based on Friedman's labour curve, which has a doubtful validity today.…”
Section: Relevance Of Partogram In Contemporary Practicementioning
confidence: 66%
“…Some of the things that affect the low recording in partographs are the level of knowledge of midwives about partographs which is not very influential in monitoring labor, recording documents and reporting partographs, making clinical decisions and planning future actions. During this time reporting and documentation by midwives was based on recording in partographs on paper, however, based on several studies said that there were still many midwives who did not complete the data in the partograph well and systematically, therefore a recording system, faster reporting and documentation of partographs in a computer and web-based data storage to facilitate the work of midwives in storing and re-accessing current and past labor history so as to prevent the accumulation of partograph files (Baillie, Chadwick, Mann, & Brooke-Read, 2013;Kitila, Gmariam, Molla, & Nemera, 2014;Asibong et al, 2014;Anita, 2016;Andrianto, 2017;Balikuddembe, Tumwesigye, Wakholi, & Tylleskär, 2017;Bedwell, Levin, Pett, & Lavender,…”
Section: Introductionmentioning
confidence: 99%